(3EVGAI GdQGehS hEVGaI GdfGehS Ydi EVGAI GdbGehSs - (3eMeO Hf GdWjH eMeO Hf eMeO Hf eMeO GdTQbj GdaGSj GdeGdcj, CHh YHO Gddg , J (B1170 (3g`s; (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3HGH GdMGA GdegedI (B: (3bdJ (B: (3bO CHOdhgG ef GdYjf ai bhdge QjM HOd bhdge QjY heKdg bhdge (B: (3UHY dZI ai UHM hcdGgeG bdjd hcPdc de jPcQ GdLRe aUd GdgeRI s
(3BNQgG (B:s
(3ef aUd GdMGA GdegedI (B( (3ef HGH GdQGA (B) (3, bhdg (B: (3bdJ (B: (3hefg GdeKd GdPi ChQOg GdejOGfi hZjQg Ef EHQGgje GdNdjd Ydjg GdSdGe Oaf Hg , hGddg SHMGfg hJYGdi CYde s
(3GdLRA GdKGdK ef GdfSNI GdKGdKI GdSGHbIs
(3GdeNWhW ajg VHW CMjGfGs
(3Hg fXGe GdJYbjHIs
(3cJHJ YfhGfGJgG HGdeOGO GdCRQb hGdCMeQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
Keywords: (3GddZIs